Raman Spectra, Molecular Modeling and Biological Studies on Buffering Agent Metal Complexes - Saad, Fawaz; S. Abou-Melha, Khlood; M. El-Metwaly, Nashwa (Asian Journal of Chemistry, 2015)
Some transition metal complexes was prepared using a trizma buffering agent as a coordinating ligand. A slim organic compound used, produces a simple complexes serve in biological application. The complexes are investigated through elemental, thermal, spectral and molecular modeling. The general coordination binding mode of the ligand is the bidentate binding through a mononegative with Mn(II) and Cr(III) complexes, or neutral with Fe(III), Zn(II) and Cd(II) ions. The octahedral bonding distribution are proposed for all investigated metal complexes. The molecular modeling calculations reflect a shadow on comparative stability in between metal complexes. The biological investigation was concerned with the inhibition activity towards some bacteria as well as the degradation of DNA. Cadmium(II) complex displays the most insecticidal activity towards all used microorganisms. Also, all the complexes display a distinguish behavior towards DNA.